Non-doctor prescription practices among women in Tamil Nadu: understanding the attitude towards over-the-counter drugs - Nirupama, A. Y.; Sowmiya, K. R.; Ravivarman, G. (International Journal Of Community Medicine And Public Health, 2022)
Background: Even though India has a very high burden of non-doctor prescription practices, there is no regulatory body governing the availability of OTC drugs unlike the Western countries. This study was aimed at evaluating the non-doctor prescription practices and the factors keeping the population away from healthcare facilities. Methods: This was a community based cross-section study including 234 women aged 18 years and above from urban and rural field practice areas of a teaching hospital in Tamil Nadu. Data was collected using a validated and pilot tested 4-part interview process and analyzed using IBM-SPSS version 21. Results: Data analysis points towards a 61.11% prevalence of non-doctor prescription practices which showed statistically significant association with all the demographic variables except income. On further inquiry, 29.49% reported having given medications to a child (<15 years) without prescription. The quality of care score was negatively correlated to the non-doctor prescription practices (r = -0.723, p<0.001). Conclusions: The findings from this study points towards the need for further research to have a better understanding of the factors which make people choose not to visit a healthcare facility despite having knowledge about the hazards of NDPPs.